Pengaruh Profitabilitas, Struktur Aktiva, dan Ukuran Perusahaan Terhadap Struktur Modal Perusahaan pada Perusahaan Real Estate And Property yang Terdaftar di Bursa Efek Indonesia Tahun 2015 - Angrita Denziana; Eilien Delicia Yunggo (Jurnal Akuntansi dan Keuangan, 2017)
The aims of this study to examine and analyze: the association between profitability and capital structure, the association between asset structureand capital structure, andthe association between firm size and capital structure of real estate and property companies listed in Indonesian Stock Exchange (IDX) during 2015. Population of this study is real estate and property companies in 2015. Sample of this study is determined using purposive sampling method based on following criteria: real estate and property companies listed in Indonesian Stock Exchange that publish complete financial report and have all of the data needed during the study period (2015) which is published on IDX official website www.idx.co.id, with the result that 41 companies fulfill the criteria. Data is analyzed using SEM method based on Partial Least Square (PLS).Result of this study concludes that (1) profitability have a negative and significant influence on capital structure, (2) assets structure have a positive and significant influence on capital structure, and (3) company size have a positive and significant influence on capital structureof real estate and property companies listed in Indonesian Stock Exchange (IDX) during 2015.